Omega-3 Polyunsaturated Fatty Acid Supplementation Improves Neurologic Recovery and Attenuates White Matter Injury after Experimental Traumatic Brain Injury. Issue 9 (September 2013) - Pu, Hongjian; Guo, Yanling; Zhang, Wenting; Huang, Lanting; Wang, Guohua; Liou, Anthony K; Zhang, Jia; Zhang, Pengyue; Leak, Rehana K; Wang, Yun; Chen, Jun; Gao, Yanqin
Dietary supplementation with omega-3 (ω-3) fatty acids is a safe, economical mean of preventive medicine that has shown protection against several neurologic disorders. The present study tested the hypothesis that this method is protective against controlled cortical impact (CCI). Indeed, mice fed with ω-3 polyunsaturated fatty acid (PUFA)-enriched diet for 2 months exhibited attenuated short and long-term behavioral deficits due to CCI. Although ω-3 PUFAs did not decrease cortical lesion volume, these fatty acids did protect against hippocampal neuronal loss after CCI and reduced pro-inflammatory response. Interestingly, ω-3 PUFAs prevented the loss of myelin basic protein (MPB), preserved the integrity of the myelin sheath, and maintained the nerve fiber conductivity in the CCI model. ω-3 PUFAs also directly protected oligodendrocyte cultures from excitotoxicity and blunted the microglial activation-induced death of oligodendrocytes in microglia/oligodendrocyte cocultures. In sum, ω-3 PUFAs elicit multifaceted protection against behavioral dysfunction, hippocampal neuronal loss, inflammation, and loss of myelination and impulse conductivity. The present report is the first demonstration that ω-3 PUFAs protect against white matter injury in vivo and in vitro. The protective impact of ω-3 PUFAs supports the clinical use of this dietary supplement as a prophylaxis against traumatic brain injury and other nervous system disorders.